Effects of Novel Vibro-Acupuncture on Healthy Subjects and Those with Experimental and Clinical Pain as Assessed by Quantitative Sensory Testing - Kelun Wang; Dennis Boye Larsen; Silvia Ambite-Quesada; Yuan Zhang; Huilin Liu; César Fernández-de-las-Peñas; Lars Arendt-Nielsen (Journal of Acupuncture & Meridian Studies, 2021)
Background : To investigate the analgesic effects of vibro-acupuncture (VA), a novel acuvibrator was developed. Objectives: To compare the analgesic effects of VA with those of manual acupuncture (MA) and placebo acupuncture (PA) on subjects with normal sensory perception (Study I), experimentally induced acute pain (Study II), and clinical chronic pain (Study III). Methods : Thirty healthy volunteers (21 males, age: 20-30 years) participated in Study I. Fourteen healthy volunteers (8 males, age: 20-32 years) participated in Study II in which experimental pain was induced by injection of hypertonic saline. Fourteen patients suffering from unilateral epicondylalgia (9 males, age: 30-61 years) participated in Study III. All participants received VA, MA, and PA at LI4 and LI10 points in a randomized, crossover, and double-blinded manner. Quantitative sensory testing (QST) was performed on the ipsilateral forearm before and after each treatment. Data were analyzed using repeated-measures (RM) ANOVA. Results : A significantly higher vibration detection threshold (VDT) was observed after treatment of VA than after MA and PA (p < 0.001). No significant treatment effect on experimental pain intensity was detected (p > 0.086). Significantly lower pain intensity (p = 0.005) and a smaller drawing area (p = 0.011) of unilateral epicondylalgia were found after VA treatment than after PA. Conclusion : A specific effect on the VDT beyond that of MA and PA was evoked by VA. Patients with epicondylitis showed significantly lower pain intensity during VA than during PA. This study indicated that VA may be beneficial in individuals with clinical chronic musculoskeletal pain; however, further studies are needed.